5
$\begingroup$

In Nielsen's book, the Kraus operator can be attained by trace out the enviroment: $$\operatorname{Tr}_{\rm env}[\hat{U}(|\psi\rangle\otimes|0\rangle)(\langle\psi|\otimes\langle 0|)\hat{U}^\dagger]. $$ And hence we can define the Kraus operator as $\Pi_l = \langle l|\hat{U}|0\rangle$.

But why can we write the total state $|\Psi\rangle=\hat{U}(|\psi\rangle\otimes| 0\rangle)$ as $|\Psi\rangle = \sum_l(\Pi_l|\psi\rangle)\otimes|l\rangle$?

$\endgroup$

1 Answer 1

5
$\begingroup$

You have $$\newcommand{\ket}[1]{\lvert #1\rangle}U(\ket\psi\otimes\ket0) = \bigg(I\otimes \underbrace{\sum_\ell \ket\ell\!\langle\ell|}_{\equiv I}\bigg) U (\ket\psi\otimes\ket0) \\ = \sum_\ell (I\otimes \ket\ell\!\langle\ell|)U(\ket\psi\otimes\ket0) = \sum_\ell (U_{(\ell,0)}\ket\psi)\otimes\ket\ell $$ where $$\Pi_\ell\equiv U_{(\ell,0)} \equiv (I\otimes \langle\ell|)U(I\otimes\ket0).$$ To be more explicit, decomposing in components the expression you get $$ (I\otimes \ket\ell\!\langle\ell|)U(\ket\psi\otimes\ket0) = \sum_{i,j} \ket{i,j} (\langle i|\otimes\langle j|)U(\ket\psi\otimes\ket0) \\ = \sum_{i,j} \ket{i,j}\, (\langle i|\otimes I) \underbrace{(I\otimes\langle j|) U (I\otimes \ket0)}_{\equiv U_{(j,0)}} (\ket\psi\otimes I) \\ = \bigg(\underbrace{\sum_i \ket i\!\langle i| U_{(j,0)}\ket\psi }_{=U_{(j,0)}\ket\psi}\bigg) \otimes \ket j $$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge you have read our privacy policy.

Not the answer you're looking for? Browse other questions tagged or ask your own question.